2016
DOI: 10.1108/ijrdm-12-2013-0224
|View full text |Cite
|
Sign up to set email alerts
|

International firms in Africa’s food retail business-emerging issues and research agenda

Abstract: Purpose – The purpose of this paper is to describe the state of the retail sector in Sub-Saharan Africa, to point out the lack of information on some critical issues and to raise some questions about relevant topics for researchers and practitioners in the retail area for the African market. Design/methodology/approach – This paper is comprised of a comprehensive review of the literature and integrates the fragmented body of knowledge on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…Previous studies in Tanzanian indicate that new supermarkets have emerged with different food items (Nandonde, 2016). However, these new players have been unable to leverage enough resources to sustain their competitiveness.…”
Section: An Overview Of Previous Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in Tanzanian indicate that new supermarkets have emerged with different food items (Nandonde, 2016). However, these new players have been unable to leverage enough resources to sustain their competitiveness.…”
Section: An Overview Of Previous Studiesmentioning
confidence: 99%
“…Some recent contributors to the existing knowledge in Africa include Neven et al (2006) who studied food retailing in Kenya, Abebe et al (2013) who authored the International Food Policy Research Institute report for Ethiopia, Emongor (2008) who studied retailing in Southern Africa Development Community region, and Weatherspoon and Reardon (2003) who investigated the implications of rising of supermarkets for agri-food system and rural poor in Kenya. In Tanzania, studies on this area focused on the factors used by retailers in the selection of suppliers (Nandonde and Kuada, 2016b), the types of food stocked in supermarkets (Snyder et al , 2015), and retailers pricing strategy (Rutashobya, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The effectiveness of development aid (Nandonde and Kuada, 2017); transmission of international food prices (or imported inflation) to African markets (Furceri et al 2016;Van Weezel, 2016;Fiamohe et al, 2015); the role of value chains in agricultural business (Ndyetabula et al, 2016) and the composition of agricultural productivity (Mohamed et al, 2016). Noticeably, missing is that the literature on the nexus between foreign aid and agriculture has not assessed whether ODA for agriculture and rural development is relevant in increasing productivity in agriculture.…”
mentioning
confidence: 99%
“…Shahidullah and Haque (2010) proposed a closer linkage between the producers and processors through vertical integration in the value chain for a reasonable price, quality, lead time and overall control of the supply chain. Lamont (1992) discussed the concept of the vertical and horizontal integration for the potato seed industries in The Netherlands and Northern Ireland whereas similar kinds of such studies are reported in the literature such as business relationship improvement (Hadjikhani and Thilenius, 2005;Gebauer et al, 2007), vertical integration (Nugent and Hamblin, 1996;Cook, 1997;Howe, 1998;Jennings, 2001;Leach et al, 2001;Charlebois and Camp, 2007;Gueimonde-Canto et al, 2011;Lamprinopoulou and Tregear, 2011;Dabas et al, 2012;Ding and Mahbubani, 2013), level of vertical integration selection (Priyadarshi and Routroy, 2018), comprising of subtopics such as strategic management (Parker et al, 2015), internationalization of retailing for rural entrepreneurs (Mudambi, 1994;Muñiz-Martínez, 1998;Johansson, 2002;Aygün and Oeser, 2017;Satyam et al, 2017), distribution (Brockman and Morgan, 1999), strategic ties (Orozco Quintero and Berkes, 2010;Dunham et al, 2012;Yi et al, 2012;Mehrotra and Verma, 2015), rural entrepreneurship (Saunders and Bromwich, 2012), economic performance (Peyrefitte et al, 2002), women entrepreneurship (Khera and Nayak, 2009;Yadav and Goyal, 2015;Bhardwaj, 2018) and improved information exchange among the supply chain members (Trim and Lee, 2006;Nandonde and K...…”
Section: Literature Reviewmentioning
confidence: 99%
“…The positive attitude towards farming and entrepreneurship (AFE) at rural areas is prerequisite to develop vertical integration of AVSC at the village level. The farming and entrepreneurship should not only be confined to AV but also it should be practiced for different agriculture produces, so that Trim and Lee, 2006;Shahidullah and Haque, 2010;Pangriya, 2015;Nandonde and Kuada, 2016; and field visits both farmer and entrepreneur will be able to get work and revenue throughout the year.…”
Section: Attitude Towards Farming and Entrepreneurshipmentioning
confidence: 99%